Enhanced control of the turbulent flow past a circular cylinder with rotating rods inspired by an inviscid solution. (August 2022) - Carvalho, I.A.; Assi, G.R.S.
Abstract: This paper examines an active mechanism of wake control for a turbulent flow regime of Reynolds number 1000 through finite volume, three-dimensional DES simulations. Eight peripheral rods equally spaced about a central body are forced to spin around their axes in two arrangements: case 0, with uniform rotation speed and case 1, with rotation rates inspired by the solution of the potential flow around the body. The two cases were constrained to the same input kinetic energy for every set of rotations. We have found case 1 to be more effective to control the wake, eliminate turbulent structures, and attenuate mean drag and fluctuating lift. The interference of the rods in the flow past the main body resulted in a steady wake in both cases, provided enough rotation was supplied to the system. This result was previously achieved only in laminar regime. Novel to such a system, rotations midway between a vortex wake and a steady wake led streamwise vortices to show a mode-B-like mechanism of vorticity transfer. Case 1 generally suppressed vortex shedding with lower input kinetic energy and required less power than case 0, thus resulting in a more efficient configuration to suppress vortices in the wake. Graphical abstract: